Association of Medicare Advantage Star Ratings With Racial and Ethnic Disparities in Hospitalizations for Ambulatory Care Sensitive Conditions. Issue 12 (10th December 2022) - Park, Sungchul; Werner, Rachel M.; Coe, Norma B.
Abstract : Background: Enrollment in high-quality Medicare Advantage (MA) plans, measured by a 5-star quality rating system, was lower among racial and ethnic minority enrollees than White enrollees partly due to fewer high-quality plans available in their counties of residence. This may contribute to racial and ethnic disparities in ambulatory care sensitive condition (ACSC) hospitalizations. Objective: We examined whether there were racial and ethnic disparities in ACSC hospitalizations among MA enrollees overall and by star rating. Methods: Using the Medicare enrollment and claims data for 2016, we identified White, Black, Hispanic, and Asian/Pacific Islander enrollees in MA plans. We estimated racial and ethnic disparities in ACSC hospitalizations (per 10, 000 enrollees) overall and by star rating. Results: We found that the adjusted rates of ACSC hospitalizations were significantly higher among Black enrollees than White enrollees overall [39.4 (95% confidence interval: 36.3–42.5)]. However, no significant disparities were found among Hispanic and Asian/Pacific Islander enrollees. The adjusted rates of ACSC hospitalizations were higher in lower-rated plans than higher-rated plans in all racial and ethnic groups. The significant disparities in ACSC hospitalizations by star rating were the most pronounced between White and Black enrollees. We found suggestive evidence that enrollment in lower-rated plans was associated with higher disparities in ACSC hospitalizations between White and Black enrollees. Conclusions: Substantial disparities in ACSC hospitalizations exist between White and Black enrollees in MA plans, especially for lower-rated plans. Policies aimed at reducing racial disparities in ACSC hospitalizations could include improving access to high-rated plans.